Advances in Therapeutic Cholangioscopy - Tomazo Antonio Prince Franzini; Renata Nobre Moura; Eduardo Guimarães Hourneaux de Moura (Gastroenterology Research and Practice)
Nowadays, cholangioscopy is an established modality in diagnostic and treatment of pancreaticobiliary diseases. The more widespread use and the recent development of new technologies and accessories had renewed the interest of endoscopic visualization of the biliary tract, increasing the range of indications and therapeutic procedures, such as diagnostic of indeterminate biliary strictures, lithotripsy of difficult bile duct stones, ablative techniques for intraductal malignancies, removal of foreign bodies and gallbladder drainage. These endoscopic interventions will probably be the last frontier in the near future. This paper presents the new advances in therapeutic cholangioscopy, focusing on the current clinical applications and on research areas.